(untitled) (Economics and region, 2019)
Attention is focused on the fact that precondition of providing social and economic development and competitiveness of domestic economy is an enterprise functioning. A variety of approaches to the issue are analyzed; it should be noted that domestic experience of entrepreneurship and the history of world leaders commercial success convincingly prove that entrepreneurial activity is one of the main drivers that determine competitiveness of economic systems, including regional one, their development and economic security. According to author’s approach, entrepreneurial activity economic security is a set of external and internal conditions under which a reliable protection of its economic interests from influence of potential and real threats is achieved, and is able to maintain stable functioning and steady development. It is proved that enterprise economic security is characterizes by a system enabling preventing various threats and hazards, protects the enterprise economic interests and keeps loses within acceptable limits. A system of entrepreneurial activity economic security is investigated as the one being created individually for each business entity based on the defined aim and objectives as well as competitiveness, market advantages and industry field etc. its functioning depends first of all on legislative support, material, technical and financial resources, on the staff skills and experience and on the person in charge of an enterprise economic security.The dialectics of an enterprise economic security and entrepreneurial activity economic security interaction is reveled. There is the necessity of directed policy on economic processes state regulation implementation in the context of realizing the stated strategies for social and economic development of the country, which has to be primarily focused on protection the rights and interests of business entities, their protection from illegal actions.